Isosorbide mononitrate for preinduction cervical ripening at or post-term pregnancy: randomised placebo-controlled clinical trial - Ramy Mohamed El-Naggar; Ahmed Nagy Shaker; Mohamed Attia Raslan; Heba Rady El-Bassyouny (Gynecology and Obstetrics Clinical Medicine)
Introduction Effective labour induction is marked by the onset of uterine contractions, progressive cervical dilation, and effacement, culminating in a vaginal birth without maternal or fetal complications. The success of induction largely depends on cervical ripening. Isosorbide mononitrate (ISMN), a nitric oxide donor, has shown potential for cervical ripening, facilitating labour induction by promoting cervical softening, effacement and dilation. This study evaluates the efficacy and safety of ISMN for cervical ripening before labour induction at term or post-term.Methods In this double-blinded randomised controlled trial, 160 primigravidas with an unripe cervix (Bishop score<6) undergoing labour induction at term or post-term were enrolled. The ISMN group received 40 mg of intravaginal ISMN in the posterior fornix every 4 hours, up to four doses. The placebo group received intravaginal pyridoxine placebos on the same schedule. The primary outcome measured was the duration from labour induction to placental delivery. Secondary outcomes included caesarean section rates.Results The ISMN group had a statistically significant shorter induction-to-delivery time compared with the placebo group (20.57±4.64 hours vs 23.15±5.13 hours, p=0.01). Additionally, the time from the first dose to delivery was reduced in the ISMN group. The caesarean section rate was lower in the ISMN group (29% vs 41%, p=0.17), though this difference was not statistically significant.Conclusion ISMN is an effective and safe option for cervical ripening, potentially shortening the labour duration.Trial registration number https://clinicaltrials.gov/study/NCT03544606.